2020
DOI: 10.1097/bot.0000000000001889
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Mortality Rate of Patients With Hip Fractures During the COVID-19 Pandemic: A Single Centre Prospective Study in the United Kingdom

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 7 publications
2
63
0
4
Order By: Relevance
“…A total of 45 studies were retrieved after the search of electronic databases using the keywords; of which, eight studies were eligible for review after screening[ 9 , 19 , 20 , 27 - 29 , 38 , 39 ] (Figure 1 ). There were three prospective studies and five retrospective comparative studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 45 studies were retrieved after the search of electronic databases using the keywords; of which, eight studies were eligible for review after screening[ 9 , 19 , 20 , 27 - 29 , 38 , 39 ] (Figure 1 ). There were three prospective studies and five retrospective comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Pooled analysis of 30-d mortality from the eight studies ( n = 1586) revealed a significantly increased death among hip fracture patients during the pandemic time (9.63% vs 6.33%; OR, 0.62; 95%CI, 0.33, 1.17; P = 0.14) (Table 3 , Figure 3 )[ 9 , 19 , 20 , 27 - 29 , 38 , 39 ]. There was no difference in 30-d mortality rate between COVID-19 negative patients who were treated during the pandemic time and all hip fractured patients treated during the pre-pandemic period (6.44% vs 5.74%; OR, 1.03; 95%CI, 0.61, 1.75; P = 0.91)[ 9 , 19 , 20 , 29 , 38 ]. However, a significant difference in mortality rate was observed between COVID-19 + and COVID-19 − patients with an OR of 6.99 (29.33% vs 5.73%; 95%CI, 3.45, 14.16; P < 0.00001) (Table 3 , Figure 3 )[ 9 , 19 , 20 , 29 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, surgery performed within 24 h of admission to patients with a hip fracture significantly reduces 1-year mortality and morbidity, while delaying surgery may increase the likelihood of 30-day mortality and complications. 34 , 36 This meta-analysis noted an increase in mortality in patients with fracture during the pandemic. Although the specific cause was not reported, the abovementioned factors are thought to have contributed to the higher proportion of deaths.…”
Section: Discussionmentioning
confidence: 95%
“…Of major concern 30-day mortality among hip fracture patients during the first 30 days of the pandemic increased. A positive Covid-19 test in patients with hip fractures is associated with a 2.4-fold increase in the risk of 30-day mortality (65).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 98%